2021
DOI: 10.1097/cce.0000000000000491
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary Exercise Testing in Critically Ill Coronavirus Disease 2019 Survivors: Evidence of a Sustained Exercise Intolerance and Hypermetabolism

Abstract: OBJECTIVES: To investigate exercise capacity at 3 and 6 months after a prolonged ICU stay. DESIGN: Observational monocentric study. SETTING: A post-ICU follow-up clinic in a tertiary university hospital in Liège, Belgium. PATIENTS: Patients surviving an ICU stay greater than or equal to 7 days for a severe coronavirus disease 2019 pneumonia and attending our post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 42 publications
(45 reference statements)
1
22
0
1
Order By: Relevance
“…Spirometry parameters ⇔ ⇓ DLCO ⇔ ⇓ (88% of pred.) Breathing reserve ⇔ O 2 pulse ⇔ (Hb NR) Deconditioning is the most common cause of impaired CRF in patients after severe COVID-19 pneumonitis Joris et al [ 16 ] N = 14 59 (10) y, 71% male 40 (18) days ex-/smoker = NR/7% diabetes = 38% Critical ( n = 14) Inclusion: surviving an intensive care unit stay > 6 days Exclusion: NR Assessed at 3 months post-discharge: O 2peak ⇓ (81% of pred.) Spirometry parameters NR DLCO NA E/ CO 2 ⇔ (mean slope: 29) HR peak ⇓ (71% of pred.)…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Spirometry parameters ⇔ ⇓ DLCO ⇔ ⇓ (88% of pred.) Breathing reserve ⇔ O 2 pulse ⇔ (Hb NR) Deconditioning is the most common cause of impaired CRF in patients after severe COVID-19 pneumonitis Joris et al [ 16 ] N = 14 59 (10) y, 71% male 40 (18) days ex-/smoker = NR/7% diabetes = 38% Critical ( n = 14) Inclusion: surviving an intensive care unit stay > 6 days Exclusion: NR Assessed at 3 months post-discharge: O 2peak ⇓ (81% of pred.) Spirometry parameters NR DLCO NA E/ CO 2 ⇔ (mean slope: 29) HR peak ⇓ (71% of pred.)…”
Section: Resultsmentioning
confidence: 99%
“…However, more than one-fourth of patients present with ventilatory inefficiency. This might be a sign of systemic alterations Joris et al [ 16 ] N = 14 59 (10) y, 71% male 40 (18) days ex-/smoker = NR/7% diabetes = 38% Critical ( n = 14) Inclusion: surviving an intensive care unit stay > 6 days Exclusion: NR Assessed at 6 months post-discharge: O 2peak ⇓ (80% of pred.) Spirometry parameters ⇔ ⇓ DLCO ⇓ (71% of pred.)…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent study, we confirmed a marked exercise limitation in critically ill COVID-19 survivors 3 months after intensive care unit (ICU) discharge, mainly related to metabolic disorders rather than cardiac or pulmonary residual impairments. The exercise limitation persisted 6 months after ICU discharge [ 11 ]. Of note, all these patients were obese, as an overweight condition and obesity were observed in most patients with severe COVID-19 [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%